Dietary inflammatory index and odds of breast cancer: A case–control study - Shatha S. Hammad (14778376) (2023)
Breast cancer (BrCA) is one of the most commonly diagnosed cancers and is the leading cause of cancer deaths in women worldwide. This study aimed to examine the association between the dietary inflammatory index (DII®) and BrCA among Jordanian women. A total of 400 adult women were enrolled into this case–control study. Cases were 200 women recently diagnosed with BrCA selected from the two hospitals that provide cancer therapy in Jordan. They were matched on age, income, and marital status with 200 BrCA-free controls. DII scores were calculated from dietary data that were collected in a face-to-face interview conducted between October 2016 and September 2017 using a validated food frequency questionnaire. Conditional logistic regression models were used to calculate odds ratios (ORs) and 95% CIs. The study results revealed no significant associations between DII scores in relation to the odds of developing BrCA after multivariable adjustment including age, education, total energy, BMI, number of pregnancy, contraceptive use, lactation, smoking, and family history of BrCA. Stratified analyses by obesity status showed that overweight/obese participants in the highest DII tertile had a >75% increased BrCA risk (OR of 1.77 [95% CI, 1.01–3.12]) compared with participants in the lowest tertile, after adjusting for age. The results from this study showed no significant relationship between the proinflammatory potential of the diet and BrCA risk in the overall study population. However, results stratified by weight category indicated an effect of diet-associated inflammation on BrCA risk in the overweight/obese group. Results of the study are consistent with a recommendation aimed at maintaining higher diet quality, that is, adopting healthy diets characterized by low DII scores in order to reduce the risk for BrCA. Other Information Published in: Food Science & Nutrition License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/fsn3.2493